SNOWBALL THROWING AND TWO STAY TWO STRAY TOWARD MATHEMATICS OUTCOMES OF EIGHT GRADE STUDENT - Eko Arif Setiawan; Nur Arina Hidayati (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
The Cooperative learning model is still rarely used as an alternative solution to overcome passive learning. This study aimed to compare the cooperative learning Snowball Throwing model and Two Stay Two Stray toward mathematics outcomes of eighth-grade students in SMP Muhammadiyah 1 Godean Sleman regency on the odd semester academic year of 2017/2018. The population in this study was eight grade students consisting of 5 classes. The sampling technique uses a random sampling technique that was by lottery class. From the lottery earned that grade VIII A class experiment as Snowball Throwing class and VIII B class experiment as Two Stay Two Stray class. Mathematics learning outcomes data obtained using the test method in the form of objective questions. Analysis of the data used analysis prerequisite and two-tailed t-test and one-tailed t-test. The test results obtained by the two-tailed t-test  = 2,4718 and  = 1,9979 mean  >  with a significance level of 5% and 67 degrees of freedom, which means  was rejected. This suggests that there were differences in mathematics achievement between students who use the cooperative model of the Snowball Throwing and cooperative model of Two Stay Two Stray. One-tailed t-test result obtained that  = 5,0423 and  = 1,6690, it means  >  with a significance level of 5% and 67 degrees of freedom, which means  was rejected. This suggests that the learning outcomes of students who use the cooperative model of Snowball Throwing were better than learning outcomes of students who use the cooperative model of Two Stay Two Stray toward mathematics of eighth-grade student SMP Muhammadiyah 1 Godean Sleman regency on the odd semester academic year of 2017/2018.